Behavior of single-box multi-cell box-girders with corrugated steel webs under pure torsion. Part I: Experimental and numerical studies. (August 2018) - Shen, Kongjian; Wan, Shui; Mo, Y.L.; Song, Aiming; Li, Xiayuan
Abstract: This paper presents the experimental and numerical studies on the full torsional behavior of single-box multi-cell box-girders with corrugated steel webs (BGCSWs) under pure torsion. Two specimens of BGCSWs with double cells and triple cells are tested under pure torsion using a new apparatus. Then the accuracy and efficiency of finite element analysis (FEA) models are validated by comparing with the experimental results, including the overall torque-twist curves, crack patterns of concrete slabs and shear strains in concrete slabs and corrugated steel webs (CSWs). Next, a parametric study is carried out, which shows that the torsional capacity is in linear proportion to the compressive strength of concrete, the thickness, yield strength and transverse position of CSWs and the number of cells in the given ranges. Besides, this study demonstrates that the CSW located at the torsional center of multi-cell BGCSWs has little effect on the torsional responses and the other inner CSWs in the multi-cell BGCSWs have little contribution to the cracking torques but have significant effects on the yield and ultimate torques. At last, a new fitted formula for the relations of smeared shear strains between the inner CSWs and the outermost CSWs is obtained from a series of case studies. Highlights: The tests of double-cell and triple-cell BGCSWs under pure torsion are conducted for the first time. A new apparatus is designed for the torsional tests. Numerical models are constructed and validated by the tests. A parametric study by FEA was carried out to investigate the effect of different parameters. A new fitted formula for the shear strain relations between the inner and outermost CSWs is obtained.